Systematic review of HIV treatment adherence research among people who inject drugs in the United States and Canada: evidence to inform pre-exposure prophylaxis (PrEP) adherence interventions - Angela R. Bazzi; Mari-Lynn Drainoni; Dea L. Biancarelli; Joshua J. Hartman; Matthew J. Mimiaga; Kenneth H. Mayer; Katie B. Biello (BMC, 2019)
Abstract Background People who inject drugs (PWID) are at increased risk for HIV acquisition and could benefit from antiretroviral pre-exposure prophylaxis (PrEP). However, PrEP has been underutilized in this population, and PrEP adherence intervention needs are understudied. Methods To inform PrEP intervention development, we reviewed evidence on antiretroviral therapy (ART) adherence among HIV-infected PWID. Guided by a behavioral model of healthcare utilization and using the PICOS framework, we conducted a systematic review in four electronic databases to identify original research studies of ART adherence in HIV-infected PWID in the United States and Canada between Jan 1, 2006-Dec 31, 2016. We synthesized and interpreted findings related to developing recommendations for PrEP adherence interventions for PWID. Results After excluding 618 duplicates and screening 1049 unique records, we retained 20 studies of PWID (mean n = 465) with adherence-related outcomes (via pharmacy records: n = 9; self-report: n = 8; biological markers: n = 5; electronic monitoring: n = 2). Predisposing factors (patient-level barriers to adherence) included younger age, female sex, and structural vulnerability (e.g., incarceration, homelessness). Enabling resources (i.e., facilitators) that could be leveraged or promoted by interventions included self-efficacy, substance use treatment, and high-quality patient-provider relationships. Competing needs that require specific intervention strategies or adaptations included markers of poor physical health, mental health comorbidities (e.g., depression), and engagement in transactional sex. Conclusions HIV treatment adherence research carries important lessons for efforts to optimize PrEP adherence among PWID. Despite limitations, this systematic review suggests that strategies are needed to engage highly vulnerable and marginalized sub-groups of this underserved population (e.g., younger PWID, women who inject drugs) in PrEP adherence-related research and programming.